From periodontal infection to oral–systemic dysbiosis: re-framing the oral microbiome’s role in systemic health and the prophylactic potential of Streptococcus salivarius probiotics - Di Pierro, Francesco; Fornaini, Carlo; Palazzi, Chiara Maria; Bertuccioli, Alexander; Tagg, John; Zerbinati, Nicola (Frontiers in Microbiology, 2025)
Since the late 19th century, the relationship between oral infections and systemic health has been widely debated. Recent advances in microbiome research suggest that oral microbial imbalance—dysbiosis—can contribute to systemic inflammatory and metabolic disorders. We propose that the term “oral-systemic dysbiosis” more accurately captures the complex interactions linking oral microbial disruption to systemic disease risk. This conceptual reframing moves beyond a purely infectious model toward a systems-based understanding of oral–body health connections. Furthermore, we hypothesize that oral administration of Generally Recognized as Safe (GRAS)-grade probiotic Streptococcus salivarius, such as strain K12, may help restore oral eubiosis and potentially reduce systemic inflammatory burden. While the hypothesis that oral probiotic maintenance may reduce the risk of systemic disorders remains to be clinically verified, defining oral–systemic dysbiosis provides a useful conceptual foundation for the exploration of integrated preventive strategies linking oral and general health.